Preparation of chemical staple fibers by plasticizing bleached coniferous pulps with 1-allyl-3-methylimidazolium chloride. Issue 14 (18th February 2021) - Qiao, Xiaolong; Lu, Hailong; Cai, Hui; Ni, Shuzhen; Zhou, Xiaofan
Abstract : In this study, we prepared chemical staple fibers (CSFs) by plasticizing bleached coniferous pulps (BCPs) with 1-allyl-3-methylimidazolium chloride (AMIMCl) under high temperature and pressure. Abstract : In this study, we prepared chemical staple fibers (CSFs) by plasticizing bleached coniferous pulps (BCPs) with 1-allyl-3-methylimidazolium chloride (AMIMCl) under high temperature and pressure. It became a transparent paper after hot-pressing when the mass ratio of AMIMCl to BCPs was 4 : 5. Interestingly, it could be hot-pressed into a new transparent paper after the transparent paper prepared above was torn into pieces. The morphologies of fibers showed that BCPs could be plasticized with AMIMCl. The glass transition temperature ( T g ) occurred in CSFs when the mass ratio of AMIMCl to BCPs was 4 : 5 and the corresponding temperature was 149 °C, which was lower than the initial decomposition temperature, therefore, CSFs could achieve workability to a certain extent. The plasticizing effect of AMIMCl on BCPs was further verified by testing the properties of the paper. The plasticizing effects of 1-butyl-3-methylimidazolium chloride (BMIMCl) and 1-ethyl-3-methylimidazolium acetate (EMIMAc) on BCPs showed the universality of the method for preparing CSFs with AMIMCl.